Sustainable Policymaking: Balancing Profitability & Sustainable Development in Businesses - Viens, Nicolas; Fortier, Denise (European Journal of Sustainable Development, 2018)
Despite multiple decades’ worth of credible data confirming the extent of sustainability problems, our society has subsequently shown very limited progress with finding viable solutions on such critical subjects. Indeed, there is growing evidence of a general misunderstanding regarding the challenges related to the climate change issue. More specifically, we point to evidence outlining sustainable development (SD) and climate change as complex meta-problems. This explains why current global environmental policies are inefficient in addressing the causes of SD and climate change and why they fail to induce sustainable practices in consumers and organizations. In this paper, we argue that the primary obstacles businesses face in adopting proper sustainable practices are found in their neoclassical business worldview and in the increased competition levels resulting from internationalization and market deregulation. To counter these obstacles, we suggest solutions that have the potential to bring true SD. First, we believe the use of specific economic tools such as sovereign funds, green investments and ethical financial indexes, can have significant effects on neoclassical businesses in stewarding them towards sustainable practices. Finally, we call for increased interdisciplinary interactions between the scientific community, policymakers and business leaders in order to better manage meta-problems related to climate change. Keywords: Sustainable development, policy, meta-problems, interdisciplinarity